5x-(5-x)=7

Simple and best practice solution for 5x-(5-x)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(5-x)=7 equation:


Simplifying
5x + -1(5 + -1x) = 7
5x + (5 * -1 + -1x * -1) = 7
5x + (-5 + 1x) = 7

Reorder the terms:
-5 + 5x + 1x = 7

Combine like terms: 5x + 1x = 6x
-5 + 6x = 7

Solving
-5 + 6x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 6x = 7 + 5

Combine like terms: -5 + 5 = 0
0 + 6x = 7 + 5
6x = 7 + 5

Combine like terms: 7 + 5 = 12
6x = 12

Divide each side by '6'.
x = 2

Simplifying
x = 2

See similar equations:

| 3x+10y=189 | | (3sinx-2)/(4sin^2x-1)-10 | | 2x+2y=3(2x+3x) | | 1.2x+3.4=2.45x-1.6 | | 8+2(4x+11)=54 | | 8+2(4x*11)=54 | | 2x=2*0.1557 | | (x/2)-(x/5)=1 | | F(x)=7x-3xfind(-2) | | 2x+11=100 | | 7-5x=x | | F(x)=7x-3x | | x+7=7x-17 | | 6x+2-3x=1 | | a+b^3= | | a/4=8=13 | | 2x/0.2-x=7.03 | | (x/2)-(x/5) | | 4x-12=10x | | 2(x+3)-11=x+5 | | 4x3/8 | | 2x+14=3x+2 | | t=2t-3(1-t) | | 4x+28=2x-1 | | a(1-x)=2ax+3-2a | | 4x-28=5x-40 | | 2(3x-5)+7=33 | | 3w-4=17 | | log16x=5/2 | | ax=a-b+bx | | -5(x-2)=40 | | -2x=1/7 |

Equations solver categories